2018
DOI: 10.1186/s12866-018-1213-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary energy levels on rumen bacterial community composition in Holstein heifers under the same forage to concentrate ratio condition

Abstract: BackgroundThe rumen bacterial community plays a critical role in feeds degradation and productivity. The effects of different forage to concentrate ratios on the ruminal microbial population structure have been studied extensively; however, research into changes in the ruminal bacterial community composition in heifers fed different energy level diets, with the same forage to concentrate ratio, has been very limited. The purpose of this study was to investigate the effects of different dietary energy levels, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
81
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(98 citation statements)
references
References 70 publications
17
81
0
Order By: Relevance
“…The study shows that phyla Proteobacteria ( R = 0.53; p = 0.04) were positively correlated with butyrate content. The genus Prevotella ( R = 0.52; p = 0.05) were also positively correlated with butyrate content, which is similar to a previous study (Bi et al, ). In contrast, Ruminococcus was negatively correlated with butyrate content ( R = −0.61; p = 0.02).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The study shows that phyla Proteobacteria ( R = 0.53; p = 0.04) were positively correlated with butyrate content. The genus Prevotella ( R = 0.52; p = 0.05) were also positively correlated with butyrate content, which is similar to a previous study (Bi et al, ). In contrast, Ruminococcus was negatively correlated with butyrate content ( R = −0.61; p = 0.02).…”
Section: Resultssupporting
confidence: 90%
“…In the present study, the phyla Proteobacteria ( R = −0.56; p = 0.03) were negatively correlated with ruminal NH 3 ‐N, while genera BF311 ( R = 0.54; p = 0.04) were positively correlated with ruminal NH 3 ‐N. Bi et al () also found that genera BF311 were positively correlated with ruminal NH 3 ‐N.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…The rumen is a complex microbial ecosystem in ruminants. It can ferment feedstuffs to volatile fatty acids (VFAs), microbial proteins and vitamins, which play important roles in animal health and production [4][5][6]. Among the microbiota, bacteria are the most abundant, diverse and metabolically active species in the rumen [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that dietary energy can promote protein to synthesize MCP [20][21][22]. The effective way to improve average daily weight gain (ADG) and production performance in cattle is increasing dietary energy levels under the same concentration of forage ratio [5].…”
Section: Introductionmentioning
confidence: 99%